Urban Forest: The Role of Improving The Quality of The Urban Environment - Dahar, Dahar; Arifin, Samsul; Nuraini, Reny; Mardikaningsih, Rahayu (Metromedia, 2022)
Urban development has consequences for the emergence of environmental problems in urban areas. With the increasing development of various activities such as road construction, transportation activities, industry, settlements and other activities, this often results in a decrease in the area of green open space and is often accompanied by a decrease in the quality of the environment. This resulted in the city becoming unhealthy, polluted and dirty. The development of green open spaces in the form of plants or green parks is needed to maintain the preservation of nature and create healthy conditions for city dwellers. Ecosystems in urban areas have urgency to be carried out immediately and carefully monitored. This paper presents important matters related to the role of urban forests in improving the quality of the environment.